INTEGRASI LOGISTIK DAN SALURAN DISTRIBUSI BERDAMPAK PADA KINERJA PERUSAHAAN LOGISTIK DI WILAYAH JABOTABEK - Lie Adek Adek (Akademi Maritim Nasional Jakarta Raya, 2020)
This study aims to determine the effect logistical integration, and distribution channels on company performance- in the Jabotabek region. This type of research uses a descriptive quantitative approach. The population of thislogistic company. The total sample of 31 respondents through www.googledocs.com The analysis was conducted using multiple linear regression with the help of SPPS 23.0 application. The results of this study indicate logistical integration (X1), distribution channels (X2) partially and simultaneously have a significant effect on the company performance (Y)